Economic Impact of Natural Disasters: An Empirical Re-examination. (February 2019) - Panwar, Vikrant; Sen, Subir
Natural disasters cause serious economic and human losses. Yet there remains ambiguity in the existing literature with regard to their impact on the economy at large. This study re-examines the relationship between natural disasters and economic growth. It aims to contribute to a fairly limited literature on the economy-wide and sector-specific consequences of natural disasters in the short-to-medium term (up to 5 years). Further, it examines whether the disaster impacts are dependent on a country's level of development. Based on panel data consisting of 102 (29 developed and 73 developing) countries over the period 1981–2015, it looks at the growth effects of four types of natural disasters, namely, floods, droughts, storms and earthquakes that were explored using the system generalised method of moments (GMM) approach. The results indicate that natural disasters have diverse economic impacts across economic sectors depending on disaster types and their intensity. The study confirms the findings of previous studies that the economic impacts of natural disasters are statistically stronger in developing countries. These findings may stimulate the policymakers especially in developing countries to explore the efficacy of viable ex-ante disaster risk financing tools (such as insurance, micro-insurance and catastrophic bonds). This would not only safeguard population and physical assets but also ensure adherence to the sustainable development goals. JEL Classification: Q54, O10